Economic evaluation of the use of saxagliptin in the treatment of type 2 diabetes in Italy - Cristiani, Marco; Citarella, Anna; Belisari, Andrea; Didoni, Guido; Mantovani, Lorenzo Giovanni; Montella, Sabato (Farmeconomia. Health economics and therapeutic pathways, 2010)
In this study we compare the cost-effectiveness of saxagliptin (Onglyza®) in combination with metformin to that of either sulphonylurea (SU) plus metformin or a thiazolidinedione  (TZD) plus metformin, in type 2 diabetes mellitus patients who are not well-controlled on metformin alone. By using decision-analytic modeling, long-term costs and health outcomes associated with the investigated treatment strategies are estimated. This is achieved by modeling the risk of experiencing diabetes-related events (e.g. myocardial infarction) or side-effects such as hypoglycemia and weight gain. The risk of these events  depends on baseline characteristics as well as risk factors (which can be altered by the treatment strategies). Ultimately, costs (NHS perspective) and quality-adjusted life years (QALYs) for each treatment strategy are based on the occurrence of these events. Based on these estimates incremental cost-effectiveness ratios (cost per QALYs) are calculated. In the analysis comparing saxagliptin + metformin with SU + metformin in 1,000 patients in a 40 years time horizon, the total QALY gain with saxagliptin + metformin is 111. The incremental cost with saxagliptin + metformin is € 1,300,000, resulting in a total cost per QALY gained with saxagliptin + metformin of € 11,800 in the base case scenario. Similarly, the comparison with TZD + metformin resulted in a total  QALY gain with saxagliptin + metformin of 127, with an incremental cost of € 144,000, resulting in a total cost per QALY gained with saxagliptin + metformin of € 1,100 in the base case scenario. The results are mainly driven by differences in hypoglycemias (associated with a utility decrement and a monetary cost) and weight gain (which is associated with a utility decrement and also increases the risk for diabetes-related events). Saxagliptin + metformin is associated with small difference in macrovascular events such as myocardial infarction, congestive heart failure compared to SU or TZD plus metformin strategies, probably due to the difference of action on net weight. Since the treatment cost is higher with saxagliptin + metformin, total costs are also higher for the Onglyza®-based strategy although the higher drug cost is partially offset by the lower rate of macrovascular costs and reduced cost of severe hypoglycemias. The present analysis suggests that saxagliptin, when added to metformin, is a cost-effective treatment alternative for type 2 diabetes mellitus patients in Italy who are not well-controlled on metformin alone. Both compared to SU + metformin and TZD + metformin, the cost-effectiveness results of saxagliptin + metformin are robust to various assumptions concerning input variables. Hence, the favorable safety profile for saxagliptin, with a risk of hypoglycemia and impact on weight similar to placebo, makes it possible to increase the utility for patients since it is not reducing risk of diabetes-related events per se.